2009
DOI: 10.2967/jnumed.109.062141
|View full text |Cite
|
Sign up to set email alerts
|

Directions and Magnitudes of Misregistration of CT Attenuation-Corrected Myocardial Perfusion Studies: Incidence, Impact on Image Quality, and Guidance for Reregistration

Abstract: CT-based attenuation-corrected (AC) myocardial perfusion imaging (MPI) studies may show significant artifacts caused by misregistration between SPECT and CT data. The present study aimed at identifying the directions and magnitudes of misregistration with greatest impact on AC myocardial perfusion image quality. Methods: The incidence, magnitude, and direction of misregistration were assessed in 248 consecutive stress-rest MPI studies in 124 patients. In addition, cardiac SPECT/CT registration was artificially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 18 publications
2
15
0
1
Order By: Relevance
“…Matsunari et al showed slight misregistration of a 7-mm shift (1 pixel) produced up to 15 % change in relatively regional uptake in the phantom study [15]. Misregistrations of more than 1 pixel were found 73 % of 248 consecutive MPS studies in the clinical study [18]. In addition, a 3-pixels misregistered shift significantly affected summed stress score for the detection of CAD. Nevertheless, misregistration induced artificial perfusions were simultaneously showed not only at the apex but also at the other regions.…”
Section: Discussionmentioning
confidence: 99%
“…Matsunari et al showed slight misregistration of a 7-mm shift (1 pixel) produced up to 15 % change in relatively regional uptake in the phantom study [15]. Misregistrations of more than 1 pixel were found 73 % of 248 consecutive MPS studies in the clinical study [18]. In addition, a 3-pixels misregistered shift significantly affected summed stress score for the detection of CAD. Nevertheless, misregistration induced artificial perfusions were simultaneously showed not only at the apex but also at the other regions.…”
Section: Discussionmentioning
confidence: 99%
“…[20, p. 174]. Unfortunately, repositioning and movement of the patient during the measurements can cause misalignments, which then result in severe reconstruction artefacts [8,15,17,18]. A mathematical approach is to solve Problem I simultaneously for attenuation and density.…”
Section: Variational Set-upmentioning
confidence: 99%
“…However, due to repositioning of the patient while being transferred from one imaging device (CT) to another (SPECT) or due to internal organ motion such as respiratory or cardiac motion, the attenuation prototype is in general inconsistent with the measured data. This can result in serious reconstruction artefacts in particular in cardiac SPECT [8,15,17,18]. To overcome these difficulties, deformable attenuation prototype is considered.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, quality control can be used to avoid reconstruction artifacts. PET/CT [28,29] and SPECT/CT [30,31] studies have shown that the frequency of misalignment can be high. Recently, it has been shown that the effects of misalignment are less severe for SPECT/CT than for PET/CT, mainly because of the low spatial resolution of SPECT [32].…”
Section: Ctac For Myocardial Spect Attenuation Artifacts In Myocardiamentioning
confidence: 99%